(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
European shot-hole borer is known to occur on a wide range of deciduous trees and frequently found on fruit trees in most of the Holarctic. During the last years increased activity of this beetle contributed necessity for investigation of it in apple orchards of Latvia. Because of the latent behavior it is difficult to control distribution of Xyleborus dispar. Often insecticides are not effective, especially if not used in an appropriate time and methods of integrated or biological plant protection are needed. In the current study, results of two year monitoring of X. dispar flying activity and effectiveness of two types of sticky traps, Rebell Rosso and Csalomon Palx, bitted with 50% alcohol are presented. Four traps of each type were placed in each orchard at the beginning of May in 2013 and at the middle of April in 2014. Differences among respective orchards were recorded: the highest number of beetles was found in the largest orchard surrounded by wide deciduous forests; the lowest number was recorded in the orchard surrounded by the agricultural lands. The first emerging X. dispar female was caught at the middle of April. During the vegetation season the highest flying activity of beetles was at the end of April - beginning of May (17th – 18th week). Afterwards number and flying activity of beetles decreased and at the middle of June (25th – 26th week) reached zero. In orchard with the highest number of European shot-hole borer, significantly higher number of beetles was recorded on Rebell Rosso traps; for the rest two orchards higher number of X. dispar was recorded on Csalomon Palx traps.